Pulmonary Hypertension and Other Potentially Fatal Pulmonary Complications in Systemic Juvenile Idiopathic Arthritis1. Issue 5 (23rd April 2013) - Kimura, Yukiko; Weiss, Jennifer E.; Haroldson, Kathryn L.; Lee, Tzielan; Punaro, Marilynn; Oliveira, Sheila; Rabinovich, Egla; Riebschleger, Meredith; Antón, Jordi; Blier, Peter R.; Gerloni, Valeria; Hazen, Melissa M.; et al.
Abstract Objective Systemic juvenile idiopathic arthritis (JIA) is characterized by fevers, rash, and arthritis, for which interleukin‐1 (IL‐1) and IL‐6 inhibitors appear to be effective treatments. Pulmonary arterial hypertension (PAH), interstitial lung disease (ILD), and alveolar proteinosis (AP) have recently been reported with increased frequency in systemic JIA patients. Our aim was to characterize and compare systemic JIA patients with these complications to a larger cohort of systemic JIA patients. Methods Systemic JIA patients who developed PAH, ILD, and/or AP were identified through an electronic Listserv and their demographic, systemic JIA, and pulmonary disease characteristics as well as their medication exposure information were collected. Patients with these features were compared to a cohort of systemic JIA patients enrolled in the Childhood Arthritis and Rheumatology Research Alliance (CARRA) registry. Results The patients (n = 25) were significantly (P < 0.05) more likely than the CARRA registry cohort (n = 389) to be female; have more systemic features; and have been exposed to an IL‐1 inhibitor, tocilizumab, corticosteroids, intravenous immunoglobulin, cyclosporine, and cyclophosphamide. Twenty patients (80%) were diagnosed with pulmonary disease after 2004. Twenty patients (80%) had macrophage activation syndrome (MAS) during their disease course and 15 patients (60%) had MAS at pulmonary diagnosis. Sixteen patients had PAH, 5 had AP, and 7 had ILD. Seventeen patients (68%) were taking or recently discontinued (<1 month) a biologic agent at pulmonary symptom onset; 12 patients (48%) were taking anti–IL‐1 therapy (primarily anakinra). Seventeen patients (68%) died at a mean of 10.2 months from the diagnosis of pulmonary complications. Conclusion PAH, AP, and ILD are underrecognized complications of systemic JIA that are frequently fatal. These complications may be the result of severe uncontrolled systemic disease activity and may be influenced by medication exposure.